The Role of Price to Book Value in Mediating the Effect of Current Ratio and Net Profit Margin on Stock Price (An Empirical Study on Broadcasting Companies Listed on the Indonesia Stock Exchange) - Saputra, Agus; Munawaroh; Rahmawantari, Dhistianti Mei (Krisnadwipayana International Journal of Management Studies, 2025)
This research aims to examine the role of market value in mediating liquidity and profitability on Stock Prices in the broadcasting industry listed on the Indonesia Stock Exchange (IDX-IC) during the 2017-2022 period. The research method employs Non-Probability Sampling with the Purposive Sampling technique. The population consists of sector E classification industries, while the targeted sample includes sub-sector E6 Media and Entertainment, Advertising, Printing & Media, specifically sub-industry E612 broadcasting media industries, with a total of five (5) industries that operate Free To Air (FTA) broadcasting. Data testing utilizes SPSS V.23 and Amos V.24. The descriptive statistics in this study adopt a quantitative approach with secondary data, and the data testing technique involves classical assumption tests, correlation tests, and regression tests using Structural Equation Modeling (SEM). The research findings are as follows: (1) The effect of the Current Ratio on Stock Prices is positive and significant, as indicated by a factor loading value of 0.232, a directional relationship value of 0.177, and a Net Profit Margin value of 0.016, which is below the significance level of 0.05. (2) The effect of the Net Profit Margin on Stock Prices is significant and negative, with a factor loading value of -0.252, a directional relationship value of -0.015, and a Net Profit Margin value of 0.032, which is below the significance level of 0.05. (3) The effect of Price to Book Value on Stock Prices is positive and significant, with a factor loading value of 0.477, a directional relationship value of 0.012, and a probability value of 0.000, which is below the significance level of 0.05. (4) The effect of the Current Ratio on Price to Book Value is negative and not significant, with a factor loading value of -0.011, a directional relationship value of -0.348, and a Net Profit Margin value of 0.896, which is above the significance level of 0.05. (5) The effect of the Net Profit Margin on Price to Book Value is positive and significant, with a factor loading value of 0.612, a directional relationship value of 1.509, and a Net Profit Margin value of 0.000, which is below the significance level of 0.05. (6) The effect of the Current Ratio on Stock Prices through Price to Book Value is negative and not significant, with a factor loading value of -0.005, a directional relationship value of -0.130, and a Net Profit Margin value of 0.896, which is above the significance level of 0.05. (7) The effect of the Net Profit Margin on Stock Prices through market value is positive and significant, with a factor loading value of 0.292, a directional relationship value of 3.491, and a Net Profit Margin value of 0.000, which is above the significance level of 0.05.